The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24018/ejmed.2020.2.3.242
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Rheumatoid Arthritis in the Elderly that attend Pilgrimage Centre, Elele, Nigeria

Abstract: This study determined the prevalence of Rheumatoid arthritis in elderly people that attended pilgrimage center, Elele Rivers state, Nigeria. A total of 200 subjects attending the pilgrimage center were examined for Rhematoid Factor using Latex agglutination method. The data was subjected to statistical analysis using Statistical Package for Social Sciences (SPSS) version 16.0. A prevalence of 4% was seen in the female subjects within the age bracket of 65-80 years and a prevalence of 1% was seen in the male su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results of a study conducted by Eledo et al [9] showed that positive Rheumatoid Arthritis occurred significantly in 5% of the population. The prevalence of this population is 4% in female subjects in the age range of 65-80 years and 1% in men in the age range of 61-70 years.…”
Section: Rheumatoid Arthritis In Elderly Womenmentioning
confidence: 95%
“…The results of a study conducted by Eledo et al [9] showed that positive Rheumatoid Arthritis occurred significantly in 5% of the population. The prevalence of this population is 4% in female subjects in the age range of 65-80 years and 1% in men in the age range of 61-70 years.…”
Section: Rheumatoid Arthritis In Elderly Womenmentioning
confidence: 95%
“…[6][7] In Nigeria, amongst the elderly that attended pilgrimage in Elele, a rheumatoid arthritis prevalence of 4% was seen among women (65-80 years) and 1% among men (61-70 years). 8 Synovitis and bone marrow oedema, are characteristics of rheumatoid arthritis at the early stage, [9][10] with suppressed immunity, cell and organ damage as symptoms at the advanced stage. [4][5] © 2024 the authors.…”
Section: Introductionmentioning
confidence: 99%